An intentional controlled islanding strategy considering island frequency stability for power system with wind-power integrated - Tang, Fei; Guo, Yuhan; Wei, Xiaoqing; Chen, Mo; Sun, Jinzhou; Deng, Huipeng (Frontiers in Energy Research, 2023)
As the last defense line to avoid cascading failures, intentional controlled islanding (ICI) is of great significance to maintain the stability of power systems. However, with the increasing penetration of renewable energy, the system inertia and primary frequency regulation capacity have significantly decreased, and the adaptability and effectiveness of ICI have also been significantly reduced. Aiming at the above problems, an ICI strategy considering island frequency stability with wind-power integration is proposed. Firstly, a basic model of ICI is constructed through the collaborative optimization of load shedding, generator tripping, and the optimal intentional islanding boundary. Secondly, a frequency response model of the islanded system considering the primary frequency regulation of wind power is established, and the corresponding linear iterative algorithm is proposed. Finally, the established frequency stability constraints are embedded into the ICI model, forming a mixed integer linear program (MILP) model. The results and the effectiveness of islanding frequency control using the proposed strategy is discussed in the IEEE39 system compared with the traditional ICI strategy.